Sustainable energy development and nuclear energy legislation in the UAE - Canal Forgues, Eric (2020)
The MENA region has been experiencing the highest population growth rate in the world since the last century. Concomitantly, energy needs in the region are projected to exceed 50% of the current demand in the upcoming two decades. The United Arab Emirates (UAE) has become the newest addition to the countries that utilize nuclear energy for electricity production. For MENA countries, UAE constitutes the model in operational and regulatory actions in their pursuit of nuclear power. UAE’s principles of transparency, nonproliferation, safety, and security, as well as its willingness to provide full operational access to international organizations, have been the key factors for this development. This study analyzes UAE’s regulatory framework with the emphasis on the organizational structure of FANR, the country’s nuclear regulatory body. Comparisons are made with USA and France, which have mature institutional structures and suggestions are provided for improving FANR’s organizational chart. Our article also discusses issues of independence and accountability of regulatory bodies, pertinent to MENA countries’ agencies.